2018
DOI: 10.1088/1361-6455/aaf2f4
|View full text |Cite
|
Sign up to set email alerts
|

Low to intermediate energy elastic electron scattering from dichloromethane (CH2Cl2)

Abstract: We report a theoretical-experimental investigation of electron scattering by dichloromethane (CH 2 Cl 2) in the low-and intermediate energy ranges. Experimental elastic differential cross sections (DCS), in the incident electron energy range of 0.5-800eV and scattering angle range of 10°-130°, were measured using a crossed beam relative flow technique. Integral and momentumtransfer cross sections were determined from the experimental DCS. Theoretical elastic differential, integral, and momentum-transfer, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 55 publications
(111 reference statements)
3
13
1
Order By: Relevance
“…1 are the TCS results from the previous measurements of Wan et al 14 and Karwasz et al, 15 along with theoretical IAM-SCAR+I and IAM-SCAR+I+rotations total cross sections of Krupa et al 12 and an SCOP result of 15 (green crosses) and theoretical IAM-SCAR+I (blue solid curve) 12 and IAM-SCAR+I+rotations (blue short dashed curve) 12 and SCOP (brown dotted curve) 16 results. The IAM-SCAR+I+rotations result when corrected for the "missing angle" effect (black dotted-dashed curve) 19 and the measured elastic ICSs of Hlousek et al 13 (red open circles) are also shown. Note that the uncertainties on the present data are statistical only.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 are the TCS results from the previous measurements of Wan et al 14 and Karwasz et al, 15 along with theoretical IAM-SCAR+I and IAM-SCAR+I+rotations total cross sections of Krupa et al 12 and an SCOP result of 15 (green crosses) and theoretical IAM-SCAR+I (blue solid curve) 12 and IAM-SCAR+I+rotations (blue short dashed curve) 12 and SCOP (brown dotted curve) 16 results. The IAM-SCAR+I+rotations result when corrected for the "missing angle" effect (black dotted-dashed curve) 19 and the measured elastic ICSs of Hlousek et al 13 (red open circles) are also shown. Note that the uncertainties on the present data are statistical only.…”
Section: Resultsmentioning
confidence: 99%
“…Naghma et al 16 The corrected, for the "missing angle" effect, IAM-SCAR+I+rotations TCSs are also given in this figure. Finally, some recent experimental elastic ICSs of Hlousek et al 13 are also included. We note that experimental elastic ICSs, over a more restricted energy range, were also reported in the work of Krupa et al 12 Those ICSs were derived from their elastic DCSs, whose angular distributions appear to be uncorrected for the "effective path length correction factor."…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations